Peran Nature Leadership dalam Membangun Keunggulan Kompetitif Pendidikan Madrasah Diniyyah - Arwani, Muhammad Ma'ruf; Rofiq, Ainur; Wafa, Ali; Aimah, Siti; Labibah, Amiroh Su’da (Instructional Development Journal, 2025)
This study aims to analyze the nature of leadership in building competitive advantages in Madrasah Diniyyah Educational Institutions with the aim of winning competition between institutions. The research location was conducted at the Madrasah Diniyyah Al Amiriyyah Blokagung Banyuwangi educational institution. A qualitative case study approach was used to uncover the phenomena that occurred in the field. Interviews, observations and documentation were used as media to collect data. Data analysis was carried out through data reduction, data display, and drawing conclusions. The results of the study indicate that the institution uses nature leadership in building competitive advantages through precise and effective strategies. Strengthening commitment, work ethic, vertical efforts and strengthening partnerships are effective strategies for leaders in leading their organizations. This study provides implications about the importance of competence, skills and other complementary aspects that must be possessed by a leader in managing their organization in order to be the best of several competitors.